SELEKSI IN VITRO UNTUK TOLERANSI TERHADAP KEKERINGAN PADA JAGUNG (Zea mays L.) DENGAN POLYETHYLENE GLYCOL (PEG) - Kaswan Badami; Achmad Amzeri (Agrovigor, 2010)
Genetic variation is a prerequisite for many breeding program that one of which can be generated through somaclon variation.  The objective of this research was to investigate effective media to induce embryo callii and to do in vitro callii regeneration for maize, and  in vitro selection was conducted by growing embryogenic callii on mediun containing polyethylene glycol (PEG).  Plant material used in this study was  5 madura cultivars i.e elos, tambin, guluk-guluk, talango and manding.   The results showed that (1) increasing addition 2,4-D on MS medium was significantly affected callii weight, however supplying 8 ppm 2,4-D was best for callii diameter, (2) The best medium to induce embryogenic callii formation was MS + 2 ppm 2,4-D + 3% manitol, (3) Increasing addition PEG  on MS medium can return the mays ES growth, and (4) A tambin and guluk-guluk cultivars was tolerance cultivars whereas manding cultivar was drought sensitive cultivar.